Impact of scientific and technological innovation on green use efficiency of urban land: A case study of 48 districts and counties in the Wuhan Metropolitan Area - ZHANG Rui, WEN LanJiao, WANG NingKe, MOU ShanShan (Ziyuan Kexue, 2023)
[Objective] The aim of this study was to explore the direction and mechanism of impact of scientific and technological innovation on urban land use efficiency, and to examine the influence of the spatial spillover effect of scientific and technological innovation on urban land use efficiency by dividing the Wuhan metropolitan area into three zones. [Methods] Based on the concept of innovation-driven green development and the theory of development zones, this study explored the impact of scientific and technological innovation on urban land green use efficiency and its mechanism. In this study, the slacks-based measure (SBM) model, panel regression model, and mediation effect model were used to analyze the zonal differences of urban land green use efficiency in 48 districts and counties of the Wuhan metropolitan area from 2010 to 2020. [Results] (1) The green use efficiency of urban land in the Wuhan metropolitan area showed an increasing trend, and the average green use efficiency of urban land in the three zones showed the following characteristics: the core areas > areas close to the core > the periphery. (2) Through the agglomeration effect and the structural effect, scientific and technological innovation had a considerable impact on the urban land green use efficiency. (3) Urban heterogeneity affected the spatial spillover effect of scientific and technological innovation through the agglomeration and configuration of input factors. Finally, the mechanism of impact of scientific and technological innovation in the three major zones was different. In the core areas, scientific and technological innovation generated the agglomeration effect and structural effect to improve the green use efficiency of urban land. In the areas close to the core, scientific and technological innovation improved the green use efficiency of urban land only through the agglomeration effect. On the periphery, scientific and technological innovation inhibited the improvement of urban land green use efficiency. [Conclusion] Scientific and technological innovation can promote the green use efficiency of urban land in the Wuhan metropolitan area, but urban heterogeneity affected the spatial spillover effect of scientific and technological innovation and influenced the green use efficiency of urban land by affecting the concentration and allocation of factors.